Spectra-based sentiment analysis - Amazonas, José Roberto; de Lima, Alexexandre Barbosa; Pereira Barretto, Marcos Roberto (INFOCOMP Journal of Computer Science, 2018)
This paper introduces a method to identify the emotions conveyed by voice signals based on spectral analysis. The adopted tool is the periodogram associated to the measurement of the cumulative energy. It is shown that the variation of the emotional state produces a shift of the spectrum that can be taken as a emotional blueprint of the speaker and can be used to track his/her mood along the time.